Pengaruh Penambahan Daun Gamal, Kelor, Dan Karbit Dalam Proses Pemeraman Pisang Kepok - Devi Tanggasari; Lusi Lukita Wardani (Jurnal Teknologi dan Mutu Pangan, 2023)
The fruit ripening process is followed by a high respiration rate and an increase in ethylene production. Carbide is used to help the ripening process but it is a chemical compound and not good for health. This study aims to study the ripening characteristics of bananas using natural ingredients that trigger ethylene in various variations in ripening time. The method used is an experimental method with a Randomized Block Design (RAK) model in the treatment using gamal leaves, moringa leaves and carbide as well as variations in curing time of 1,2 and 3 days. The results showed that there was a significant change in bananas during ripening for 1, 2 and 3 days as indicated by the parameters measured in each treatment. The ANOVA results showed a significant effect on the type of trigger and the duration of curing for each treatment. The curing temperature for 1, 2 and 3 days averaged 28.33–29.66°C in each treatment. There was an increase in each curing agent. Measurement of the treatment of gamal leaves with L values 28.96, 45.16 and 69.53, respectively. showed curing 1, 2 and 3 days on average 94-97%. The final color is indicated by the calculation of °Hue of 80.46 yellow gradient and the level of sweetness of all types of kepok banana ripening ingredients which is the best and safe for consumption using ripening Gamal leaves which from the first day to the last day has increased.